Rancang Bangun dan Analisis Penggunaan Sistem Informasi Manajemen Proyek Berbasis Free Open-Source Software (FOSS) pada Perusahaan Berskala Besar di Jawa Tengah - Bambang Widjanarko Susilo; Agustinus Wardi; Sri Heneng Prasastono; Rachmat Setyawan (Universitas Kristen Indonesia Toraja, 2022)
Design and Analysis of the Use of a Project Management Information System Based on Free Open-Source Software (Foss) in Large-Scale Companies in Central Java. To increase knowledge about project communication management and organizational communication in the cigarette industry at PT. Aman Indah Makmur, especially with regard to the use of FOSS as a tool for internal interaction and communication. Design and Analysis of the Use of a Project Management Information System Based on Free Open-Source Software (Foss) in Large-Scale Companies in Central Java. Qualitative methods were used, literature research, online ethnography, and observations were carried out to better understand important events where FOSS Google Spreadsheet users interacted, communicated, and collaborated. As the Collaboration Metric Model shows, FOSS Google Sheets can be an effective and efficient tool in large companies with 50 to 100 employees.